Pengaruh Kepatuhan Wajib Pajak Terhadap Peningkatan Pendapatan Pajak Kendaraan Bermotor Di Kantor Samsat Kabupaten Enrekang - Riswanto, Riswanto; Hakim, Lukman; Haerana, Haerana (Universitas Muhammadiyah Makassar, 2021)
The purpose of this study was to determine taxpayer compliance, increase in tax revenue and the effect of taxpayer compliance on the increase in motor vehicle tax revenue at Samsat Office of Mamuju Regency. This study used quantitative. The number of samples was 99 taxpayers registered at Samsat Office of Mamuju Regenc. Data collection techniques were observation, questionnaires and documentation. The type of research used quantitative research. The results showed that there was a direct effect of taxpayer compliance on the increase in motor vehicle tax revenue at the Samsat Office of Mamuju Regency. Based on the results of the study showed that there was a positive and significant relationship so there was an effect of tax compliance (x) on an increase in motor vehicle tax revenue (y) in the Samsat Office of Mamuju Regency by 54.9% and the remaining 45.1% was influenced by other variables not examined in this research. From the results of this study known that there were still several important indicators that still needed more attention to increase tax revenue in Mamuju Regency.